PERAN FUNGI MIKORIZA ARBUSKULA (FMA) DALAM MENINGKATKAN PERTUMBUHAN RUMPUT BEDE (Brachiaria decumbens Stapf.) PADA TANAH TERCEMAR TIMBAL (Pb) - Hazra, Fahrizal; Rosita, Risa; Tamimi, Thariq Final (JTSL (Jurnal Tanah dan Sumberdaya Lahan), 2026)
Lead (Pb) contamination in soil has a deleterious effect on agricultural land quality. Remediation using Arbuscular Mycorrhizal Fungi (AMF) and signal grass (Brachiaria decumbens Stapf.) has been identified as an effective strategy. This study aims to (1) evaluate the effectiveness of AMF on sorghum growth, (2) compare the performance of single and combined AMF applications, and (3) assess the effect of AMF on the growth of signal grass. The experiment was conducted at the SEAMEO BIOTROP Laboratory using a completely randomized factorial design with three factors: (1) Pb concentration (0, 50, 100 ppm); (2) AMF application (no AMF, Glomus fasciculatum (GF), and a combination of Glomus fasciculatum + Gigaspora margarita (GF+GM)); and (3) soil conditions (sterile and non-sterile). The results showed that AMF propagation enhanced sorghum growth, with the combination treatment (GF+GM4) performing best, while the single treatment (GF5) produced the highest spore density. Single AMF propagation (GF) was more effective for spore multiplication, whereas the multi-genus combination supported greater plant growth. The GF+GM treatment also produced optimal signal grass growth, with the highest plant height at P2F3T2 (29.33 cm) and the highest number of leaves at P2F1T1 (4.06 leaves). The mechanism of Pb accumulation in roots, its translocation to the canopy, and the role of AMF in restricting Pb ion transport while enhancing nutrient uptake demonstrate that integrating phytoremediation and bioremediation effectively reduces Pb toxicity.